THE COMMUNICATION STYLE OF THE HEAD OF THE PROTOCOL SECTION OF THE REGIONAL SECRETARIAT OF EAST JAVA PROVINCE TO MILLENNIAL AND ZILLENNIAL EMPLOYEES IN ASSISTING THE GOVERNOR’S OFFICIAL DUTIES - Arinatus S, Diah; Joko Prasetyo, Iwan (Proceeding of International Conference on Multidisciplinary Research, 2024)
A good and healthy communication process in government institutions or agencies is important to create a conducive work atmosphere. The phenomenon of how a leader's communication style becomes interesting if there is a difference that can be a source to “encourage” employees who are carrying out tasks in the field. In the government agency itself, there is a special section in charge of organizing the governor's official events, so that the role of the protocol leader becomes very important in carrying out the task. The purpose of this research is to find out how the communication style of the leader of the Protocol section of the Regional Secretariat of East Java Province. This research also uses descriptive qualitative research methods seen from the point of view of protocol employees in understanding the communication style carried out by a leader. The results showed that the communication style of the leadership of the protocol section of the East Java Provincial Secretariat was to use the Formal Communication Style, Informal Communication Style, Meangatur Communication Style and Closed Communication Style and Firm Communication Style.